2010
DOI: 10.1074/jbc.m109.074609
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42p Is Activated during Vacuole Membrane Fusion in a Sterol-dependent Subreaction of Priming

Abstract: Cdc42p is a Rho GTPase that initiates signaling cascades at spatially defined intracellular sites for many cellular functions. We have previously shown that Cdc42p is localized to the yeast vacuole where it initiates actin polymerization during membrane fusion. Here we examine the activation cycle of Cdc42p during vacuole membrane fusion. Expression of either GTP-or GDP-locked Cdc42p mutants caused several morphological defects including enlarged cells and fragmented vacuoles. Stimulation of multiple rounds of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…To induce vacuole fusion in C. neoformans, we adapted the hypotonic stress method used for S. cerevisiae (20,48). Cells grown in yeast extract-peptone-dextrose (YPD) were stained with FM4-64 either directly or after 20 min of hypotonic treatment (10-fold dilution of YPD in water) and were examined microscopically at the time points indicated in the figure legends.…”
Section: Methodsmentioning
confidence: 99%
“…To induce vacuole fusion in C. neoformans, we adapted the hypotonic stress method used for S. cerevisiae (20,48). Cells grown in yeast extract-peptone-dextrose (YPD) were stained with FM4-64 either directly or after 20 min of hypotonic treatment (10-fold dilution of YPD in water) and were examined microscopically at the time points indicated in the figure legends.…”
Section: Methodsmentioning
confidence: 99%
“…In S. cerevisiae it has been shown that actin disassembly is an early subreaction of vacuole membrane fusion, whereas the formation of F-actin is needed for fusion and is likely catalyzed by components activated by Cdc42 at the membrane surface 22 , 23 . In this yeast, overexpression of either constitutively active or dominant-negative Cdc42 resulted in vacuole fragmentation 21 . It is likely that multiple vesicle transport and fusion processes include a Cdc42-regulated actin remodeling subreaction, and the hyperactive Cdc42L160S concentrated in endomembranes might block these processes.…”
mentioning
confidence: 99%
“…Previously, we have shown the requirement for actin dynamics and turnover in membrane fusion (10), and we have linked fusiondependent actin dynamics on vacuoles with two Rho GTPases, Rho1p and Cdc42p (11)(12)(13). Cdc42p is rapidly activated during in vitro fusion reactions and stimulates the rapid polymerization of actin (11,14).…”
mentioning
confidence: 99%